Increased Expression of Fibulin-1 Is Associated With Hepatocellular Carcinoma Progression by Regulating the Notch Signaling Pathway - Gong, Jiao; Jie, Yusheng; Xiao, Cuicui; Zhou, Wenying; Li, Xinhua; Chen, Yaqiong; Wu, Yuankai; Cao, Jing; Zhang, Qi; Gao, Zhiliang; Hu, Bo; Chong, Yutian (Frontiers in Cell and Developmental Biology, 2020)
Fibulin-1, a component of the extracellular matrix (ECM), its prognostic, pathophysiologic and diagnostic role in hepatocellular carcinoma (HCC) has not yet been reported. We first found that either Fibulin-1 messenger RNA (mRNA) or protein expression was highly overexpressed in HCC tissues compared with normal tissues, which was associated with overall survival. Moreover, Fibulin-1 was an independent prognostic predictor for overall survival (p= 0.001). Furthermore, Overexpression or inhibition of Fibulin-1 reduced or sensitized HCC cells to apoptotic signals, and Fibulin-1 silencing suppressed the ability of HCC cells to form tumors in vivo. Moreover, Fibulin-1 inhibited apoptosis via the Notch pathway while Fibulin-1 silencing had no obvious effect on p-MAPK, p-c-jun and p-stat3 expression, and both Mcl-1 and Bcl-xL are targets of Fibulin-1. Furthermore, the stromal and immune score was elevated in high Fibulin-1 tissues, and FBLN1 expression was associated with increased infiltrating macrophages using xCELL, TIMER and TISDIB tool based on TCGA HCC database. Importantly, the circulating cell-free RNA (cfRNA) level of Fibulin-1 in the serum were significantly increased in patients with HCC compared with those in healthy controls, individuals with chronic hepatitis B and patients with HBV-induced liver cirrhosis. The area under receiver operating characteristic curves (AUC) was 0.791 for Fibulin-1, 0.640 for a-fetoprotein and 0.868 for the combination of the two tumor markers. Our findings indicate that Fibulin-1 may be a potential prognostic indicator, a promising serum biomarker and a therapeutic target in patients with HCC.